2020
DOI: 10.1155/2020/8871745
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light Irradiation Induces Human Keratinocyte Cell Damage via Transient Receptor Potential Vanilloid 1 (TRPV1) Regulation

Abstract: Although blue light has been reported to affect skin cells negatively, little is known about its action mechanisms in skin cells. Therefore, we investigated the role of the transient receptor potential vanilloid 1 (TRPV1) in blue light-induced effects on human keratinocytes and its underlying mechanisms. Blue light decreased cell proliferation and upregulated TRPV1 expression. Blue light also suppressed the epidermal growth factor receptor- (EGFR-) mediated signaling pathway by reducing the protein levels of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…It affects not only various signaling pathways, but also increases the level of pro-inflammatory cytokines and differentiation, and reduces proliferation. The authors demonstrated that the increase of TRPV1 caused EGFR destruction, which led to the inhibition of AKT/GSK3β/FoxO3a signaling, and in the end to the decrease of keratinocytes proliferation [ 25 ]. Thus, the main theory is that blue light via chromophores has an impact on proliferation and differentiation [ 23 ].…”
Section: Antiproliferative and The Anti-inflammatory Properties Of Blue Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…It affects not only various signaling pathways, but also increases the level of pro-inflammatory cytokines and differentiation, and reduces proliferation. The authors demonstrated that the increase of TRPV1 caused EGFR destruction, which led to the inhibition of AKT/GSK3β/FoxO3a signaling, and in the end to the decrease of keratinocytes proliferation [ 25 ]. Thus, the main theory is that blue light via chromophores has an impact on proliferation and differentiation [ 23 ].…”
Section: Antiproliferative and The Anti-inflammatory Properties Of Blue Lightmentioning
confidence: 99%
“…Similarly, Yoo et al demonstrated that blue light caused a rise of ROS release, which was dependent on transient receptor potential vanilloid 1 (TRPV1). They also found that blue light increased proinflammatory cytokine TNF-α production by activating of activator protein 1 (AP-1) and nuclear factor κB (NF-κB) [ 25 ]. In the study investigating the ROS formation following phototherapy, Nakashima et al found that blue light caused oxidative stress in human keratinocytes.…”
Section: The Negative Aspects Of Blue Lightmentioning
confidence: 99%
“…The maintenance of an appropriate moisture content in the SC contributes to SC maturation and skin desquamation [ 25 ]. On the contrary, abnormally increased TEWL impairs various enzymatic activities required for normal barrier formation and desquamation, leading to accelerated skin aging and induction of skin diseases [ 26 ]. Therefore, maintenance of proper water content in the keratinocyte is essential for normal skin homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemistry analysis was conducted as previously described [ 25 ]. Specifically, while for fixation, cells were treated with 4% paraformaldehyde in PBS for 15 min, they were incubated with 0.1% Triton X-100 and 0.01% Tween-20 for 20 min at room temperature for the permeabilization.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time polymerase chain reaction (RT-PCR) analysis was conducted as previously described [ 25 ]. Specifically, RT-PCR analysis was done with an ABI7900HT Instrument (Applied Biosystems, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%